The Moderating Role of After-Sales Service on Product Quality, Brand Image, and Used Car Repurchase Intention - Saputra, I Gede Harry Pratama; Indiani, Ni Luh Putu; Setini, Made (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
Purpose – This paper seeks to examine the effect of product quality and brand image on repurchase intention of used car consumers in Denpasar, Bali, as well as to analyze the moderating role of after-sales service in strengthening these relationships. Methodology/approach – A quantitative survey approach was employed to collect data from 120 consumers who had previously purchased used cars and received after-sales services from used car showrooms in Denpasar. The data were gathered through a Likert-scale questionnaire and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). Findings – The results indicate that product quality and brand image have a positive and significant influence on consumers repurchase intention. However, after-sales service does not moderate the relationship between product quality and repurchase intention, nor between brand image and repurchase intention. These findings suggest that repurchase decisions in the used car market are mainly driven by the physical condition of the vehicle and brand perception rather than by post-purchase services. Novelty/value – This study provides insight into consumer repurchase behaviour in the used car industry in Bali, emphasizing the importance of maintaining vehicle quality and strengthening brand image as key strategies for used car showrooms. Although after-sales service was not found to play a moderating role, it remains important as a supporting factor for customer satisfaction and long-term relationships.